Nutrition - Spence, Annette; Orlandi, Mario; Prue, Donald (New York : Facts on File, 1988)
Provides information on all aspects of exercise, including methods to measure and improve physical fitness.
A Friedman Group book--T.p. verso.;Includes index.
Keywords: Exercise; Nutrition; Physical fitness